Evaluating the effectiveness of the eRNA technique in monitoring fish biodiversity – A case study in the Qingdao offshore, China - Wenqiong Li; Hui Jia; Hui Zhang (Global Ecology and Conservation, 2024)
With the continuous intensification of human activities, fish biodiversity has been reduced in the Yellow Sea. Therefore, accurate monitoring methods are crucial for determining fish biodiversity in the target area. The environmental DNA (eDNA) technique has emerged as a promising non-invasive method, but it is prone to false positives. The rapid degradation of environmental RNA (eRNA) has the potential to reduce false positives in the eDNA technique; however, there is limited research on using the eRNA technique to study fish biodiversity. This study aimed to explore a suitable sampling method for extracting sufficient eRNA from seawater samples. Furthermore, we performed a case study in Qingdao offshore, China, to survey fish species and community composition based on the eRNA and eDNA techniques in November 2022 using seawater samples collected from 19 sampling sites. We compared the results with data obtained through traditional field survey (TFS) methods and examined the relationship between fish species and environmental factors. The results revealed a significant overlap between fish species detected by the eRNA and eDNA techniques, with the eRNA technique demonstrating higher sensitivity and positive predictivity, and fewer false positives compared to those of eDNA. Our study highlighted the potential of the eRNA technique as a powerful tool for improving the detection rate of fish species in marine ecosystems.